2022
DOI: 10.3390/diagnostics12071582
|View full text |Cite
|
Sign up to set email alerts
|

TOX Expression in Mycosis Fungoides and Sezary Syndrome

Abstract: Mycosis fungoides (MF) and Sezary syndrome (SS) are the two most common type of cutaneous T-cell lymphoma (CTCL). Currently, no markers can be clearly related to prognosis or to differential diagnosis between early stages and inflammatory benign diseases (IBD). The thymocyte selection-associated high mobility group box factor (TOX), has been proposed as a possible marker in differential diagnosis between early CTCL stages and IBD. Recently TOX has been related to prognosis. We aimed to investigate whether TOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…[12][13][14][15] However, TOX expression has been recently reported to be not specific to neoplastic T lymphocytes but also seen in reactive lymphocytes found in BIDs. [44][45][46] Consistent with the studies that challenged the original reports, TOX expression was observed in both MF and BIDs, and TOX seemed to have no diagnostic value for eMF. ) and is involved in the differentiation of naive T cells into Th1.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…[12][13][14][15] However, TOX expression has been recently reported to be not specific to neoplastic T lymphocytes but also seen in reactive lymphocytes found in BIDs. [44][45][46] Consistent with the studies that challenged the original reports, TOX expression was observed in both MF and BIDs, and TOX seemed to have no diagnostic value for eMF. ) and is involved in the differentiation of naive T cells into Th1.…”
Section: Discussionsupporting
confidence: 78%
“…The original and subsequent several studies showed that TOX expression was significantly increased in eMF, whereas it was negative or weakly increased in BIDs, and TOX was proposed as a diagnostic marker for eMF 12–15 . However, TOX expression has been recently reported to be not specific to neoplastic T lymphocytes but also seen in reactive lymphocytes found in BIDs 44–46 . Consistent with the studies that challenged the original reports, TOX expression was observed in both MF and BIDs, and TOX seemed to have no diagnostic value for eMF.…”
Section: Discussionmentioning
confidence: 84%
“…(i) Negative: no staining, (ii) +1 (mild): <10%, (iii) +2 (moderate): 10% to 30%, (iv) +3 (strong): >30% 14…”
Section: Methodsmentioning
confidence: 99%
“…(i) Negative: no staining, (ii) +1 (mild): <10%, (iii) +2 (moderate): 10% to 30%, (iv) +3 (strong): > 30%. 14 ICOS cytoplasmic expression in epidermal exocytotic lymphocytes and/or dermal lymphocyte was evaluated as 0 = no staining, low expression = 5%, moderate expression = 5% to 50%, high expression = > 50% of cells stained positive. 7 GATA-3 nuclear expression intensity in epidermal exocytotic lymphocytes and/or dermal lymphocyte was evaluated as (no staining = 0, mild staining = 1, moderate staining = 2, strong staining = 3).…”
Section: Evaluation Of Tox Icos and Gata-3 Immunostainingmentioning
confidence: 99%